PEDAGOGICAL MODELS OF BLENDED LEARNING: TYPOLOGY, EFFICIENCY, CONDITIONS OF IMPLEMENTATION (Innovative professional education, 2024)
The article presents a generalized experience of the transition to distance, in particular, mixed education in the conditions of the war between Russia and Ukraine. An approach to the typology of blended learning models is considered, which can be implemented at different levels: curriculum, subject, section or topic (within the subject). The scientific characteristics of the most widespread models of blended learning, which can be used in professional education, are given.
Keywords: blended learning, learning models, blended-learning, professional training